찰옥수수 한발 스트레스에 대한 살리실산과 앱시식산의 처리 효과 - 서영호; Youngho Seo; 박기진; Kijin Park; 장은하; Eunha Chang; 류시환; Sihwan Ryu; 박종열; Jongyeol Park; 김경희; Kyunghi Kim (Korean journal of crop science, 2014)
Climate change may result in greater risk of yield reduction of waxy corn due to drought stress and maize is one of the sensitive crops to the soil moisture shortage. While irrigation is the most effective practice to reduce the drought damage, farmers are unable to apply water due to limited water resource and irrigating facilities. The study was conducted to investigate the application effect of salicylic acid and abscisic acid on reducing drought stress of waxy corn (Zea mays L.). Drought stress was imposed by withholding irrigation from 9 days before anthesis to 14 days after anthesis. Salicylic acid or abscisic acid was applied on tasseling date at concentration of 0.5 mM and 0.1 mM, respectively. Drought stress increased anthesis-silking interval (ASI) by 3.0~3.3 days and decreased plant height, ear length, ear diameter, number of rows in ear, and yield by 47~51 cm, 4.6~5.0 cm, 4.4~5.3 mm, 1.5~2.0, and 2.4~2.5 Mg/ha, respectively. Application of salicylic acid and abscisic acid did not significantly reduced the drought injuries of waxy corn. Pretreatment of the plant growth regulators before water deficit stress or divided application at low concentration may be required to obtain the reduction effect on drought stress of waxy corn.